2021
DOI: 10.1021/acschemneuro.0c00762
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Dependent Changes of miRNA Levels in the Hippocampus of Adrenalectomized Rats Following Acute Corticosterone Administration

Abstract: We explored sex-biased effects of the primary stress glucocorticoid hormone corticosterone on the miRNA expression profile in the rat hippocampus. Adult adrenalectomized (ADX) female and male rats received a single corticosterone (10 mg/kg) or vehicle injection, and after 6 h, hippocampi were collected for miRNA, mRNA, and Western blot analyses. miRNA profiling microarrays showed a basal sex-biased miRNA profile in ADX rat hippocampi. Additionally, acute corticosterone administration triggered a sex-biased dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 109 publications
0
3
0
Order By: Relevance
“…Since an integral aspect of our analysis was to compare miRNA results across studies with diverse test systems, it’s important to highlight the complexities of comparing miRNA findings across studies with different patient disease backgrounds or differences between in vivo and in vitro disease models. The type of test system (human, in vivo , or in vitro ), species, sex, genetic background, chemical exposure, disease conditions, and biological matrices could all contribute to diversity in miRNA responses when comparing across studies ( Corrales et al , 2021 ; Harrill et al , 2016 ; Razak et al , 2013 ; Wang et al , 2009 ). We believe that an integrative approach, utilizing both chemically induced and disease model miRNA data is necessary to identify relevant miRNA biomarkers that will be useful for predictive safety in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Since an integral aspect of our analysis was to compare miRNA results across studies with diverse test systems, it’s important to highlight the complexities of comparing miRNA findings across studies with different patient disease backgrounds or differences between in vivo and in vitro disease models. The type of test system (human, in vivo , or in vitro ), species, sex, genetic background, chemical exposure, disease conditions, and biological matrices could all contribute to diversity in miRNA responses when comparing across studies ( Corrales et al , 2021 ; Harrill et al , 2016 ; Razak et al , 2013 ; Wang et al , 2009 ). We believe that an integrative approach, utilizing both chemically induced and disease model miRNA data is necessary to identify relevant miRNA biomarkers that will be useful for predictive safety in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating research evidences suggest that excessive induction of CORT levels by stress events causes cellular damage and is strongly implicated in the pathogenesis of depression. 19,20) Other studies also indicate that hippocampal neuronal proliferation and growth play crucial roles in the pathological mechanism of depression, so the damage of neuronal cell survival and development caused by CORT exposure can be an effective way to establish a model of depression. 21,22) PC-12 cell line is a neural cell line derived from rats, which is widely used in the study of nervous system diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of sex on miRNA expression has been increasingly studied in the adult brain [20][21][22][23][24][25][26][27] , but few publications address sex-differential miRNA expression during development. Ziats et al (2014) showed sex differences in miRNA expression in the human brain from before birth to adulthood 28 .…”
Section: Introductionmentioning
confidence: 99%